Dynamics of Students' Ideas about the Work in the Arctic - V. V. Sharok; Yu. А. Yakovleva; N. A. Vakhnin (Moscow Polytechnic University, 2021)
The article presents the results of the longitudinal study, which was conducted during the years 2018 and 2019 and aimed to identify changes in the assessment of certain socio-economic and psychological aspects of working and living in the Arctic by students of different courses. Special attention was paid to such factors as transport and social infrastructure, working conditions, wages, social guarantees, the climate, health status, the psychological atmosphere in a team, the possibility of self-realization. The sample population at the first stage of the study was 618 people (2018). After bringing the 2019-sample in line with the parameters of the 2018-sample, 337 students' questionnaires were analyzed in the second stage. The main research method was a questionnaire survey, the results of which were statistically processed using such methods as the qualitative analysis of the empirical data, the analysis of primary statistics, the analysis of contingency tables (for nominative data), comparative and variance analyses (for metric data). The software "Statistica" was used for statistical processing. The main results of the study, first of all, include an increase in internal motivation to work in the Arctic among the students from the 2019-sample: they, to a greater extent, compared to junior students, emphasize the need for personal interest in work. The analysis of the answers of the respondents in year 2019 showed an increasing role of wages and the understanding of difficult climate conditions and the associated difficulties of living in deciding whether to work in the Arctic. In other words, the longitudinal study, implemented during the years 2018 and 2019, recorded the obvious increase in motivation, as well as the increase in the requirements for working and living conditions in the harsh Arctic climate among the surveyed students during their transition to the senior year.